From Cultural Heritage to Emerging Economic Crop: State Agricultural Policy and Local Hemp Development in Khiri Rat Subdistrict, Phop Phra District, Tak Province, Thailand - Pounpunwong, Wasan (Journal of Thai Studies, 2026)
Background and objective (s): Hemp (Cannabis sativa L.) has been an integral part of the cultural heritage, domestic economy, and textile practices of Hmong communities in northern Thailand. Recently, hemp has been repositioned within Thailand’s Bio-Circular-Green (BCG) policy framework as a strategic economic crop. This study aimed to achieve two objectives: (1) to analyze the agricultural policies of the Thai government regarding the promotion of hemp as a developing economic crop in Khiri Rat Sub-district, Phop Phra District, Tak Province; and (2) to investigate the impact of these policies on sustainable capacity building, collective strengthening, and market development among hemp-growing farmer groups in the area of study. Methodology: This study used a qualitative case study approach, combining the analysis of existing documents with fieldwork. The sources for this documentary analysis came from a variety of places. These included policy documents, legal and regulatory texts, district and provincial development plans, official reports, research reports, academic books, journal articles, and publications from relevant public and private organizations. Fieldwork was carried out from April to July 2025 following the ethics approval granted by the Human Research Ethics Committee of Pibulsongkram Rajabhat University (COA No. 023/2025). The final sample included thirteen participants, chosen purposefully from three groups: those involved in policy and institutions, those in network and community enterprises, and those who grew hemp or were involved in community enterprises. Data collection involved semi- structured, in-depth interviews, field notes , pho tographs, an d site observati ons. Thematic content analysis and methodological triangulation were used to analyze the data. Main result: The findings show that Thailand’s hemp policy, particularly under the Action Plan for the Development of the Hemp Industry toward Commercialization, 2023–2027, reflects a developmental and policy-coordination approach through targeted regulation, institutional support, and value-chain planning. In Khiri Rat, hemp development is supported by favorable geography, agro-ecological suitability, and longstanding Hmong expertise. However, implementation remains incomplete. Major constraints include complex licensing procedures, uneven access to technical and regulatory knowledge, limited processing infrastructure, fragmented inter-agency coordination, and unstable market channels. Relevance to Thai Studies: This study contributes to Thai Studies by demonstrating how hemp has shifted from a culturally embedded Hmong plant to a state-promoted economic crop within contemporary Thailand’s BCG regime. This research links cultural capital, public policy, and borderland development, and shows how state strategy, ethnic livelihoods, and market rationalities are negotiated in a peripheral yet strategically significant region. Conclusion: The study concludes that Thailand has made progress in establishing a strategic framework for hemp development, but its effectiveness remains constrained by uneven state capacity, fragmented institutional mechanisms, limited infrastructure, and uncertain market formation. Sustainable hemp development in border ethnic communities requires not only legal liberalization, but also accessible licensing, stronger community enterprises, integrated value-chain governance, and the strategic integration of traditional Hmong knowledge with modern standards, branding, and market innovation.